HASBI ASH-SHIDDIEQY'S THOUGHTS IN THE PEARL OF HADITH: INTERTEXTUAL ANALYSIS OF IDEA - Ahmad Fibrianto; Jannatul Husna; Waharjani Waharjani (Profetika: Jurnal Studi Islam, 2023)
It is hoped that this research can decide how to examine the intertextual ideas of Hasbi Ash-Shiddieqy's thoughts in one of his works, the pearl of hadith. From researching his work entitled "2002 Pearls of Hadith", the considerations he made in searching for hadith in the pearls of hadith, were as follows: 1) Hadith was understood through the guidance of the Qur'an, 2) Musykil hadiths in takwil , 3) Looking for agreement on conflicting traditions. Researchers see that in every study so far, Hasbi has always emphasized the use of a historical socio-cultural approach, or what is commonly called a logical approach, but in this study, the researcher tries to see Hasbi's point of view from an intertextual approach. Where the function of hadith in the Koran is always considered and also seen in other traditions that have similar topics and other traditions that seem problematic. This research is qualitative literature (library research), then the data processing stage and analyze the data that has been collected, the author uses the descriptive analysis method